Effects of an HIV Positive Diagnosis During Pregnancy on Mother Baby Bonding at Selected Health Facilities in Lusaka District Zambia - Sianchapa, Brenda Nambala; Katowa-Mukwato, Patricia; Ngoma, Catherine M. (British Journal of Healthcare and Medical Research, 2024)
Background: Mother-baby bonding sets the stage for the growing child to enter healthy relationships with other people throughout life and to appropriately experience and express a full range of emotions. The stress of a diagnosis of HIV during pregnancy can lead to unsuccessful mother-baby bonding. Aim: The study aimed to describe the effects of an antenatal HIV positive diagnosis on mother-baby bonding. Methodology: A qualitative descriptive cross-sectional study design was used. Purposive sampling was used to select 17 study participants on whom in-depth interviews were conducted to collect data. Data were analysed using thematic analysis. Major findings: The majority of participants reported positive mother-baby bonding. After thematic analysis, one main theme; mother-baby interactions with three subthemes; mother-baby relationship, hurdles to mother-baby bonding and cause of baby’s death, emerged. Most of the participants reported feelings of attachment to their babies, with babies responding positively to the care by their mothers. Majority of them breastfed, which enhanced the mother-baby bond. However, some of them reported negative bonding and constant fear of infecting their babies. Some participants reported that the stress of an antenatal HIV diagnosis led to pregnancy complications, which led to loss of their babies. Conclusion: Some participants reported negative bonding and some lost their babies due to pregnancy complications that were caused by stress of an antenatal HIV diagnosis. The study recommends assessing women for stress and categorising their coping strategies to assist those with high stress levels or those utilising negative coping in order to enhance mother-baby bonding.